2007
DOI: 10.17161/foec.v40i1.6863
|View full text |Cite
|
Sign up to set email alerts
|

School Violence and Disruption Revisited: Equity and Safety in the School House

Abstract: In the September, 2000. issue of Foctts on E.xceptianal Children, we, along with several colleagues, examined .school violence and related disorders through ecological and other perspectives (Leone. Mayer. Malmgren. & Meisei. 2000). That article attempted to move beyond a discussion limited to child-centered characteristics and toward the contexts of children's lives. Our analysis of school violence examined family structure and poverty, exposure to violence in popular tnedia. access to guns, and influences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…Although perpetration may be a learned behavior, ocial skills deficits may also indicate that students with disabilities who engage in bully perpetration could have ocial information processing deficits (Crick & Dodge, 1994;Crick & Dodge, 1996;Dodge et al , 2003). More specifically, a lack of social skills may be related to the lack of assertion, a lack of self-control, or both (Mayer & Leone, 2007). Students with disabilities might also misread social cues , misinterpret social stimuli, or respond with aggression toward peers (Sabornie, 1994 ).…”
Section: Personal Characteristicsmentioning
confidence: 99%
“…Although perpetration may be a learned behavior, ocial skills deficits may also indicate that students with disabilities who engage in bully perpetration could have ocial information processing deficits (Crick & Dodge, 1994;Crick & Dodge, 1996;Dodge et al , 2003). More specifically, a lack of social skills may be related to the lack of assertion, a lack of self-control, or both (Mayer & Leone, 2007). Students with disabilities might also misread social cues , misinterpret social stimuli, or respond with aggression toward peers (Sabornie, 1994 ).…”
Section: Personal Characteristicsmentioning
confidence: 99%
“…An educational institution is responsible for creating a communicative environment to facilitate students' positive personal and academic growth where their safety and equality are ensured [1]. However, it has been pointed out by Skrzypiec et al (2011) [2] that school bullying is threatening such establishments; and there have been more and more records of peer-on-peer abuse cases that require immediate responses [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a few students responded by self-concealing, retaliating, reporting directly to law enforcement, or complaining with certain people about the bully Mendes (2011) [16], or calling the police [17]. Other researchers, namely Mayer and Leone (2007) [1]; Rigby (2020) [18]; Smith (2013) concluded that the victims feel helpless confronting their abusers [17]. Research findings by Dobarro (2011) [19]; Nguyen-Thi et al (2014) [20]; Pérez-Fuentes et al (2011) [21]; Totura et al (2009) [8] showed the negative correlation between academic performance and violent behaviors, that is, students with violent behaviors had poor academic performance, and academic performance of those suffering from bullying was also negatively affected as well.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing literature showed the multi-level occurrence of violence, the individual, peer, family, school, and national levels [20][21][22] . It has been recommended not to study the violence on individual level, but to study the context of school violence as a whole or in a comprehensive view 9,23 .…”
Section: Schoolviolence Overviewmentioning
confidence: 99%